(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Territorial Use Rights for Fisheries-Reserve (TURF-Reserve) is a form of rights-based fisheries management that could improve the effectiveness and coral reef conservation efforts in Marine Protected Area (MPA). Maya Tribe Customary Council with Mayalibit Bay customary communities declared Customary Fisheries Management (CFM), a fishery resources management approach that combines customary marine tenure, traditional ecological wisdom, and TURF-Reserve principles. This study aims to measure coral reef health conditions to illustrate CFM’s effectiveness in maintaining coral reef conditions in Mayalibit Bay. This study uses Point Intercept Transect (PIT) and fish belt transect as data collection methods to gather coral reef health data. Coral reef condition is measured using five indicators with ecological thresholds. Study results show that there is an increase of reef fish biomass and herbivore fish biomass proportion compared to previous condition which indicate a healthy coral reef ecosystem. Decreasing macroalgae: hard coral ratio along with fished: unfished ratio compared to previous condition indicate coral reef ecosystem with moderate condition. This study concluded that the coral reef ecosystem in Mayalibit Bay is in healthy condition and its reef fisheries activities are still considered sustainable. Based on the healthy coral reef condition, CFM is shown as an effective approach in maintaining coral reef ecosystem condition, complementing conservation efforts, and reef fishery resources management in Mayalibit Bay.